Disease Modeling and Phenotype Rescue Using Inducible Pluripotent Stem Cells from Patients with Diamond-Blackfan Anemia - Bhoopalan, Senthil Velan; Han, Min-Joon; Ellis, Steven; Lesmana, Harry; Estepp, Jeremie H.; Jang, Yoonjeong; Weiss, Mitchell J.; Wlodarski, Marcin W. (Blood, 2019)
Diamond-Blackfan anemia (DBA) is a congenital ribosomopathy and bone marrow failure syndrome manifesting typically in infancy with erythroid hypoplasia. Approximately half of affected individuals also have developmental anomalies. Over time, additional cytopenias can develop, including reduced hematopoietic stem and progenitor cells (HSPC). Heterozygous loss-of-function mutations in over 20 ribosomal protein (RP) genes cause approximately 70% of DBA cases, although only 7 genes (RPS19, RPL5, RPS26, RPL11, RPL35a, RPS24 and RPS7) account for over 90% of patients with a known DBA genotype. Medical therapies including steroids, chronic transfusions are partially effective but have considerable side effects. Hematopoietic stem cell transplantation (HSCT) from matched related or unrelated donors is curative with recently reported good outcomes, although many patients lack a suitable donor and/or have serious treatment-related comorbidities that increase HSCT-related toxicities. Case reports of spontaneous genetic reversion in DBA suggest that RP gene-corrected HSPC have competitive advantage over RP-deficient cells, thus providing the rationale for gene therapy as a feasible therapeutic approach. Induced pluripotent stem cell (iPSC) technology provides a robust model of human disease and can recapitulate hematopoietic defects encountered in bone marrow failure syndromes. The goals of this study was to establish a culture system from patient-derived iPSCs that can recapitulate key aspects of DBA pathophysiology and provide a preclinical model for gene manipulation to correct the abnormal phenotype (Figure 1). We developed iPSCs from individuals with DBA who were enrolled on INSIGHT (NCT02720679), an IRB-approved, prospective study that includes biobanking of peripheral blood mononuclear cells (PBMNC) from patients with bone marrow failure syndromes. We first reprogrammed these DBA PBMNC into iPSCs using non-integrating Sendai virus to establish lines with pathogenic mutations in RPS19 (c.191>T, p.Leu64Pro), RPS19 (c.184C>T, p.Arg62Trp), RPL11 (c.61dupT, p.Cys21Leufs*13), and a variant of uncertain significance (VUS) in RPS7 (c.277_279delGTC, pVal93del). Undifferentiated iPSC lines exhibited abnormal ribosomal biogenesis revealed by polysome profiling and pre-rRNA analysis. Upon in vitrodifferentiation to hematopoietic lineages, the mutant iPSCs recapitulated DBA phenotypes with reduced CD34+ HSPCs, near absence of erythroid colonies (BFU-E and CFU-E) colonies and failure to produce erythroid cells in liquid culture. We used two methods to correct single nucleotide RP mutations in DBA iPSCs (Figure 1): i) CRISPR/Cas9-mediated homology-directed repair, and ii) base-editing, which utilizes catalytically inactive Cas9 fused to a deaminase that interconverts nucleotides directly in the absence of double-stranded DNA breaks. Corrected “isogenic” lines showed phenotype similar to wild type controls, with restored erythroid differentiation, and normal polysome maturation and pre-rRNA ratios. Because some patients carry large intragenic or whole RP gene deletions that are not amenable to gene correction, we also explored the feasibility of gene rescue by inserting a wild type copy of the defective gene (Figure 1). Using zinc-finger nuclease (ZFN), we inserted wild type RP cDNA constructs into the “safe harbor” AAVS1 locus on chromosome 19, thereby rescuing abnormal phenotypes of patient-derived iPSC lines with RPS19(p.Arg62Trp) and RPL11(p.Cys21Leufs*34) mutations. Additionally, we explored lentiviral gene delivery as an alternative method for RP gene replacement. We compared different promoters including MND, PGK and EF1a and found that the latter was most effective at rescuing RP gene expression in iPSC cells. Transduction of lentiviral vectors with wild type RPS19or RPL11fused to the EF1a promoter into three iPSC lines with RPS19or RPL11mutations resulted in stable transgene expression of RPS19or RPL11genes and phenotypic rescue. This study supports the feasibility of establishing iPSCs from DBA subjects with different genotypes. These iPSC lines provide a useful resource for numerous studies of DBA including preclinical approaches to gene therapy, evaluating the pathogenicity of RP gene variants of unknown significance and examining the pathophysiology of RP haploinsufficiency. [Display omitted] Estepp:Esperion: Consultancy; Forma Therapeutics: Research Funding; Global Blood Therapeutics: Consultancy, Research Funding; Pfizer: Research Funding; Eli Lilly and Co: Research Funding; Daiichi Sankyo: Consultancy. Weiss:GlaxoSmithKline: Consultancy; Rubius Inc.: Consultancy; Cellarity Inc.: Consultancy; Beam Therapeutics: Consultancy; Esperion: Consultancy.